Public Access for Pheasant Hunters: Understanding an Emerging Need. Issue 1 (6th November 2019) - Wszola, Lyndsie S.; Madsen, Anastasia E.; Stuber, Erica F.; Chizinski, Christopher J.; Lusk, Jeffrey J.; Taylor, J. Scott; Pope, Kevin L.; Fontaine, Joseph J.
ABSTRACT: Ring‐necked pheasant ( Phasianus colchicus ; i.e., pheasant) hunting participation is declining across North America, reflecting a larger downward trend in American hunting participation and threatening benefits to grassland conservation and rural economies. To stabilize and expand the pheasant hunting population, we must first identify factors that influence pheasant hunter participation. We used an extensive in‐person hunter survey to test the hypothesis that hunter demographics interact with social‐ecological traits of hunting locations to affect hunter decisions, outcomes, and perceptions. We built a series of Bayesian mixed effects models to parse variation in demographics, perceptions, and hunt outcomes of pheasant hunters interviewed at public access hunting sites across 3 regions in Nebraska, USA, that varied in pheasant abundance and proximity to urban population centers. Among pheasant hunters in Nebraska, access to private lands was negatively related to the human population density of a pheasant hunter's home ZIP code and the distance a hunter had traveled to reach a hunting location. Pheasant hunters interviewed closer to metropolitan areas tended to be more urban and travel shorter distances, and their parties were more likely to include youth but less likely to include dogs. Hunter satisfaction was positively associated with seeing and harvesting pheasants and hunting with youth. Whereas youth participation and the number of pheasants seen varied by study region, hunter satisfaction did not differ across regions, suggesting that hunters may calibrate their expectations and build their parties based on where they plan to hunt. The variation in hunter demographics across hunting locations and disconnects between social and ecological correlates of hunter satisfaction suggests that diverse pheasant hunting constituencies will be best served by diverse pheasant hunting opportunities. © 2019 The Wildlife Society. Abstract : Public access hunting sites in ecologically rich rural areas attracted ring‐necked pheasant hunters from farther distances, who were more likely to hunt with dogs and less likely to hunt with youth. Sites near urban areas, however, attracted local urban hunters and fostered greater youth participation. Satisfaction was equivalent across all regions, suggesting that public access hunting programs may best serve hunters with diverse backgrounds and objectives through a diverse portfolio of hunting opportunities.